Aortic Stiffness Index And Carotid Intima-Media Thickness Are Independently Associated With The Presence Of Microalbuminuria In Patients With Type 2 Diabetes Mellitus - Turan Y (Dove Medical Press, 2019)
Yaşar Turan,1 Elif Turan2 1Department of Cardiology, Medical School of Bozok University, Yozgat, Turkey; 2Department of Endocrinology and Metabolic Disease, Medical School of Bozok University, Yozgat, TurkeyCorrespondence: Yaşar TuranBozok University, Cardiology, Yozgat 66200, TurkeyTel +903542127050Fax +903542126201Email yasar044@yahoo.comPurpose: Microalbuminuria is a premature and widely used indicator of diabetic nephropathy and is reported to be related with a higher cardiovascular risk in diabetic patients. We aimed to examine whether the echocardiographic parameters, such as epicardial fat thickness (EFT), carotid intima-media thickness (CIMT) and aortic stiffness index (ASI) are associated with microalbuminuria in patients with diabetes mellitus type 2 (T2DM).Patients and methods: A total of 272 consecutive patients were enrolled and after the exclusion criteria, the data of 180 patients with T2DM were used in this cross-sectional study. Patients were divided into two groups: 82 patients with microalbuminuria and 98 patients without microalbuminuria (normoalbuminuria). The laboratory results and echocardiographic EFT, CIMT and ASI parameters were noted.Results: Compared with the normoalbuminuria group, EFT, CIMT and ASI were significantly higher in the microalbuminuria group (p<0.05 for all). In logistic regression analysis; CIMT (OR: 3.15, p=0.024) and ASI (OR: 4.19, p=0.016) were independently associated with microalbuminuria in patients with T2DM.Conclusion: In addition to CIMT, as a novel finding, ASI which is an indicator for the elastic properties of the aortic root was independently associated with microalbuminuria. CIMT and ASI measurement by echocardiography may be helpful in identifying the accompanying factors in the development of nephropathy.Keywords: aortic stiffness, carotid intima-media thickness, microalbuminuria